Cultural correlates of national innovative capacity: a cross-national analysis of national culture and innovation rates - Youngsun Jang; Youngjoo Ko; So Young Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
Although it is conventional wisdom that innovation requires free mind, diversity, or creativity all of which are closely associated with political and organizational decentralization, it is in fact more politically centralized countries in East Asia that successfully capitalized on innovation to catapult their economies onto the growth trajectory. Scholars have thus wondered if this is an exception rather a rule. Are more centralized countries innovative? Existing empirical research has produced mixed results. This study introduces a new perspective on this issue. Rather than the degree of centralization found in formal institutions, we focus on non-institutional or informal dimensions of centralization particularly associated with culture. Using Hofstede's cross-national dataset capturing national culture, we explore how different dimensions of national culture are linked to national innovative capacity as proxied by patents. Our preliminary findings from the analysis of 34 OECD member states based on the patent data extracted from the Patent Cooperation Treaty (PCT) database suggest that non-institutional dimensions of centralization account more for the variations in national rates of patents per capita than more formal aspects of centralization measured by traditional political datasets such as POLCON. While cultural aspects have been examined in technology management at the individual and the firm level, this study fills a gap in the existing literature by exploring their relationship at the national level. More research is clearly needed to explore the roles of non-institutional features facilitating or hampering innovation.
Keywords: 650; Authoritarianism; Culture; Democracy; Decentralization; Development; Innovation; Patent; Technology